(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Dimethacrylates of 1,4-aminonaphthole and 1,5-aminonaphthole have been synthesized and their reactivity in conditions of radical polymerization have been investigated. Kinetic parameters of their polymerization are similar to the values of corresponding parameters obtained for dimethacrylates based on 4-aminophenole and 4-(2-aminoethyl)phenole. In contrast with phenyldimethacrylates, linear soluble polymer products could be obtained up to 70 % conversion.